The Bandung City Public’s Knowledge Of The Covid-19 Hoax News With Media Literacy (Using Descriptive Study) - Arsyi Fadhillah Zulkarnain; Roro Retno Wulan (SEIKO : Journal of Management & Business, 2021)
In 2020, there is a Corona Virus Disease from Wuhan, China. This virus eventually spread throughout the world. The Covid-19 pandemic caused a tsunami information, because there is so much information about Covid-19 without knowing which information is correct. The tsunami information that is not yet known to be true is a bad thing and will be vulnerable to being a hoax, hoax is fake news. A person's media literacy ability can be an anticipating the spread of the Covid-19 hoax. Media literacy is the ability to know various forms of media and understand their uses. Using a quantitative method with a cluster sampling technique, this research reveals the knowledge of Bandung City’s People regarding the Covid-19 hoax with media literacy. Based on the mean value of 80.47%, which means that this study proves that public knowledge about hoaxes is in a good position. The analysis obtained from respondents who answered YES by 1529/80.47%, the rest answered NO by 456/19.5%. So it shows the knowledge of Bandung City’s People of the Covid-19 Hoax with Media Literacy in the good category, which means, the people of Bandung City have good knowledge in analyzing news on social media about the Covid-19 Hoax. Keywords: Hoax, Covid-19, Media Literacy